Comparison of Omadacycline and Tigecycline Pharmacokinetics in the Plasma, Epithelial Lining Fluid, and Alveolar Cells of Healthy Adult Subjects - Gotfried, Mark H.; Horn, Karolyn; Garrity-Ryan, Lynne; Villano, Stephen; Tzanis, Evan; Chitra, Surya; Manley, Amy; Tanaka, S. Ken; Rodvold, Keith A. (Antimicrobial agents and chemotherapy, 2017)
The steady-state concentrations of omadacycline and tigecycline in the plasma, epithelial lining fluid (ELF), and alveolar cells (AC) of 58 healthy adult subjects were obtained. Subjects were administered either omadacycline at 100 mg intravenously (i.v.) every 12 h for two doses followed by 100 mg i.v. every 24 h for three doses or tigecycline at an initial dose of 100 mg i.v. followed by 50 mg i.v. every 12 h for six doses. A bronchoscopy and bronchoalveolar lavage were performed once in each subject following the start of the fifth dose of omadacycline at 0.5, 1, 2, 4, 8, 12, or 24 h and after the start of the seventh dose of tigecycline at 2, 4, 6, or 12 h. The value of the area under the concentration-time curve (AUC) from time zero to 24 h postdosing (AUC 0–24 ) (based on mean concentrations) in ELF and the ratio of the ELF to total plasma omadacycline concentration based on AUC 0–24 values were 17.23 mg · h/liter and 1.47, respectively. The AUC 0–24 value in AC was 302.46 mg · h/liter, and the ratio of the AC to total plasma omadacycline concentration was 25.8. In comparison, the values of the AUC from time zero to 12 h postdosing (AUC 0–12 ) based on the mean concentrations of tigecycline in ELF and AC were 3.16 and 38.50 mg · h/liter, respectively. The ratio of the ELF and AC to total plasma concentrations of tigecycline based on AUC 0–12 values were 1.71 and 20.8, respectively. The pharmacokinetic advantages of higher and sustained concentrations of omadacycline compared to those of tigecycline in plasma, ELF, and AC suggest that omadacycline is a promising antibacterial agent for the treatment of lower respiratory tract bacterial infections caused by susceptible pathogens.